Cooperative Learning Strategies for Engaging History Education: Exploring GI and TGT Models - Syahputra, Muhammad Ilham; Djono, Djono; Azmi, Muhammad (Yupa: Historical Studies Journal, 2025)
History learning is considered boring learning for students, this learning is considered less useful because it is identical to memorization, therefore educators must have expertise in mastering learning methods and models so that learning in the classroom becomes not boring. This writing aims to see the relevance of the Group Investigation (GI) and Team Game Tournament (TGT) learning models. The method used in this article is descriptive qualitative. Qualitative descriptive research method is one type of analysis that explains a phenomenon or data obtained. The phenomenon or data is obtained from books, journals, and articles with collection techniques namely editing, organizing, and finding. The results of the analysis conducted by the author regarding the definition of GI and TGT, then the relevance of GI and TGT in learning history. The conclusion of this writing is that by using interesting and interactive learning models such as GI and TGT, history learning which is considered boring will become interesting learning for students.